Dysregulation of Pseudogenes/lncRNA-Hsa-miR-1-3p-PAICS Pathway Promotes the Development of NSCLC. (30th August 2022) - Song, Yichen; Wang, Zhiying; He, Lewei; Sun, Feidi; Zhang, Beilei; Wang, Fu
Abstract : Objective . Non-small cell lung cancer (NSCLC) explains about 80 percent of whole lung cancers, and its 5-year survival rate is impoverished, as when people are first diagnosed, 68% of whom are identified at a dangerous stage. The molecular mechanisms of NSCLC are still being explored. Methods . GSE18842 and GSE19804 were exerted to scan for diversely expressed genes (DEGs) in NSCLC, and then we used GEPIA for the validation of DEGs expression. The prognostic values were determined through Kaplan–Meier analysis. Three target prediction databases indicated potential microRNAs (miRNAs), while miRNet predicted hsa-miR-1-3p′s upstream long non-coding RNAs (lncRNAs) and pseudogenes. UALCAN was utilized to identify the co-expressed genes of PAICS, while enrichment analysis on them was managed with Enrichr. Results . We initially found that the gene expression level of cyclin B1 (CCNB1), cyclin-dependent kinases1 (CDK1), and phosphoribosylaminoimidazole succinocarboxamide synthetase (PAICS) had a notable increase in NSCLC. We predicted 6, 10, and 7 microRNAs to target CCNB1, CDK1, and PAICS, respectively. Among miRNA-mRNA (microRNA-messenger RNA) pairs, we deduced that the hsa-miR-1-PAICS axis was the most potential one to inhibit the occurrence of NSCLC. We also noted that the hsa-miR-1-3p-PAICS axis participated in regulating the process of mitosis with mechanical functions. Moreover, we identified 5 pseudogenes and 33 long non-coding RNAs (lncRNAs) that might inhibit the hsa-miR-1-3p-PAICS axis in NSCLC. Conclusions . The pseudogene/lncRNA-hsa-miR-1-3p-PAICS is very important in NSCLC on the basis of this study, thus providing us with effective treatments and promising biomarkers for the diagnosis of NSCLC.